2020
DOI: 10.1111/1759-7714.13327
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnosis and treatment recommendations for ocular toxicities of targeted therapy and immune checkpoint inhibitor therapy

Abstract: The increased use of targeted therapy and immune checkpoint inhibitors in cancers has brought new hope of survival to patients with advanced tumors. However, increasing numbers of immune‐related adverse events (irAEs) of these medications have been reported, affecting almost all human organs including the eye. These adverse effects may affect the entire ocular region, including the eyelid, eye lashes, conjunctiva, cornea, uvea, retina and optic nerve, and have thus far been largely ignored by patients and doct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 33 publications
(81 reference statements)
0
14
0
8
Order By: Relevance
“…Although ocular irAEs are infrequent based on the previous study, they can cause a deterioration of the quality of life and exert an influence on the compliance of patients. Lots of studies have reported the ocular adverse events secondary to ICIs (19,25,26,30,31,153,(164)(165)(166)(167)(168) and the grade of the adverse events had been published recently based on Common Terminology Criteria for Adverse Events. While no study had reported the ocular irAEs in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Although ocular irAEs are infrequent based on the previous study, they can cause a deterioration of the quality of life and exert an influence on the compliance of patients. Lots of studies have reported the ocular adverse events secondary to ICIs (19,25,26,30,31,153,(164)(165)(166)(167)(168) and the grade of the adverse events had been published recently based on Common Terminology Criteria for Adverse Events. While no study had reported the ocular irAEs in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Aufgrund der Kombination aus granulomatöser Uveitis, schwerer Chorioiditis mit Aderhautamotio, exsudativer Ablatio retinae und exsudativer Makulopathie gehen wir auch bei unserem Patienten von einer bilateralen Vogt-Koyanagi-Haradaartigen Uveitis aus. Diese kann als Nebenwirkung von Immun-Checkpoint-Inhibitoren nur einzelne Komponenten des Vogt-Koyanagi-Harada-Syndroms aufweisen [8]. Die Uveitis war unter systemischer Kortikosteroidtherapie rückläufig.…”
Section: Verlaufunclassified
“…Such adverse events may be more severe than their spontaneously occurring counterparts and they may run a different clinical course . Checkpoint‐induced myasthenia gravis has been shown to be lethal in one‐third of all cases ; anti‐acetylcholine antibodies are usually not detectable. Patients and their families should be informed about this type of adverse events, especially given the fact that neurological symptoms may be lethal if detected too late or not at all .…”
Section: Organ‐specific Adverse Events During Immune Checkpoint Blockadementioning
confidence: 99%